Dinamika in ravni cen izdelkov za vsakdanjo rabo - Jagrič, Timotej (IB revija (Ljubljana), 2009)
After the introduction of the euro, prices in Slovenia started to rise. It was a phenomenon known from other EMU members, but for a certain period, the growth of prices in Slovenia was higher than in other euro countries even though prices in these countries were affected by world prices in a similar way. Many economists considered the price growth a result of market imperfection, oligopoly and monopolistic behavior of certain suppliers. This paper analyses Mercator's products, as Mercator has the highest market share in retail trade. The results are divided into three parts: in the first, the price dynamics of the most traded Mercator's products are compared with the statistical indexes of Slovenia, in the second, Mercator's prices are compared with prices of the same or similar products in Austria, and in the third both views are synthesized in a comparative analysis of price levels in the period of the last three years.
Keywords: cene; gibanje cen; indeks cen; življenjske potrebščine; trade; trgovina; trgovina na drobno